A new system to the spectroscopy analysis with multiple X-ray of free electron laser - Thair Abdulkareem Khalil Al-Aish; Hanady Amjed Kamil
The primary goal of this paper is the possibility of improving spectroscopy analysis using a new mechanism that has the ability to detect small crystalline defects and the fast transitions that occur within electronic states, which contributes significantly to the development of various fields and applications of scientific knowledge. The working mechanism is summed up by obtaining two laser pulses with specific specifications within the x-ray range, by creating an executive program (SAMXFEL) using the MATLAB program for the purpose of simulation. This system allows the investigation of rapid changes in the structure of matter. By analyzing the simulation results, two pulses of electron lasers were obtained with wavelengths ranging from (0.316535, 0.114399) nm and powers (927686, 927683) watts, in addition to pulse durations   within (1.05512, 0.38133) atto-seconds that ensures that the target material is protected from damage. The proposed system in this paper is mainly based on the spectral and spatial separation of the two pulses to interpret the scattered and diffracted X-rays. The spatial separation allows multiple X-ray pulses to be emitted from different angles of the sample. X-ray diffractography using multiple simultaneous pulses from different angles becomes possible without loss of photon energy generated by the spectrometer.